(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the use of innovative educational technologies in foreign language teaching, the role of innovative educational technologies in the education system, the positive role of students in learning a foreign language, as well as improving the quality and effectiveness of educational processes in remote areas and, innovative methods and new ideas are proposed